The Czechoslovak airman in the Soviet internation during the World War II (Theatrum historiae, 2013)
This article described the story of the Czechoslovak airmen who fell into the Soviet captivity of autumn 1939. After the occupation of the Czech lands almost 700 members of flying personnel escaped to Poland. Most of them were transported to France but 190 airmen remained in Poland. After outbreak the War 115 airmen were captured by the Red Army. These men went through several internment camps. The life conditions inside these lagers were horrors. The leadership of Czechoslovak foreign action deals with the Soviet authorities about releasing airmen. During the years of 1940 and 1941 were airmen transported to France and England. The last group came to England in the spring of 1942.
Keywords: Czechoslovak airmen; foreign resistance; World War II; Poland; Germany; Soviet Union; internation; Red Army; repatriation